Application of pH indicator labelling for monitoring the quality of mango ‘Nam Dok Mai See Thong’ in modified atmosphere packaging - W. Kumpoun (2019)
© 2019 International Society for Horticultural Science. All rights reserved. Fresh fruit storage is very important for the exporter in order to keep the fruit in good quality. Modified atmosphere packaging is one of the useful methods but it can cause fruit fermentation, abnormal ripening and off flavours. The application of the pH indicator label for monitoring ‘Nam Dok Mai See Thong’ mango fruit in modified atmosphere packaging was investigated. ‘Nam Dok Mai See Thong’ mango fruit, sized 300-400 g, were packed individually in a zip locked polypropylene bag with 4, 6, 8 and 10 holes (0.5 mm diameter hole-1). The pH indicator label for monitoring quality was applied in all bags. All fruit was stored at 11°C for 3 days (mimicking transportation time). The fruits were removed and allowed to ripen at 25°C. Changes of the label colour were observed and gas condition in the package and the quality of mango fruit was determined. The results found that the mango fruit in packages where the indicator label colour did not change colour, showed normal ripening. The fruit in packages that had the indicator label where the colour changed, displayed fermentation and high concentrations of carbon dioxide and ethanol. By increasing the number of holes the abnormal ripening could be prevented. The results indicate that the use of pH indicator labels, combined with the modified atmosphere packaging, were able to indicate and inform the seller to open the package in order to prevent the fruit from abnormal ripening. Moreover, 85% of consumers accepted packaging with indicator labels.